Carbonized Bamboos as Excellent 3D Solar Vapor‐Generation Devices. Issue 4 (12th December 2018) - Bian, Yue; Du, Qianqian; Tang, Kun; Shen, Yang; Hao, Licai; Zhou, Dong; Wang, Xiaokun; Xu, Zhonghua; Zhang, Huiling; Zhao, Lijuan; Zhu, Shunming; Ye, Jiandong; et al.
Abstract: Given the global challenges of water scarcity, solar‐driven vapor generation has become a renewed topic as an energy‐efficient way for clean water production. Here, it is revealed that bamboo, as a natural hierarchical cellular material, can be an excellent 3D solar vapor‐generation device by a simple carbonization progress. A floating carbonized bamboo sample evaporates water with an extremely high vapor‐generation rate of 3.13 kg m −2 h −1 under 1 sun illumination. The high evaporation rate is achieved by the unique natural structure of bamboos. The inner wall of bamboo recovers the diffuse light energy and the thermal radiation heat loss from the 3D bamboo bottom, and the outer wall captures energy from the warmer environment. The high evaporation rate is also attributed to reduced vaporization enthalpy of water confined in the bamboo mesh. Such bamboo‐based high‐performance, low‐cost, self‐cleaning, solid durable, and scalable 3D vapor‐generation device has attractive applications in desalination as well as industrial and domestic wastewater abatement. Abstract : Carbonized bamboos can enable excellent solar vapor generation (3.13 kg m −2 h −1 under 1 sun illumination), as the water confined in the hierarchically nanostructured bamboo mesh possesses reduced latent heat and the macroscopic 3D structure gains energy from the environment. Such a bamboo‐based 3D vapor‐generation device has attractive applications in desalination as well as industrial and domestic wastewater abatement.